Efficacy of the induced pluripotent stem cell derived and engineered CD276-targeted CAR-NK cells against human esophageal squamous cell carcinoma - Lin, Xiaolan; Guan, Tian; Xu, Yien; Li, Yun; Lin, Yanchun; Chen, Shaobin; Chen, Yuping; Wei, Xiaolong; Li, Dongsheng; Cui, Yukun; Lin, Yan; Sun, Pingnan; et al. (Frontiers in Immunology, 2024)
Chimeric antigen receptor natural killer (CAR-NK) cells have been found to be successful in treating hematologic malignancies and present potential for usage in solid tumors. In this study, we created CD276-targeted CAR-expressing NK cells from pluripotent stem cells (iPSC CD276-targeted CAR-NK cells) and evaluated their cytotoxicity against esophageal squamous cell carcinoma (ESCC) using patient specific organoid (PSO) models comprising of both CD276-positive and CD276negative adjacent epithelium PSO models (normal control PSO, NC PSO) as well as primary culture of ESCC cell models. In addition, in vitro and in vivo models such as KYSE-150 were also examined. iPSC NK cells and NK-free media were used as the CAR-free and NK-free controls, respectively. The efficacy of the iPSC CD276-targeted CAR-NK cells was demonstrated by their successful treatment of CD276-expressing ESCC in a multitude of pre-clinical models, implying that they hold tremendous therapeutic potential for treating patients with CD276-expressing ESCC.